Literature Review Formulasi Sediaan Masker Clay Antioksidan - Dona Indriastuti; Mentari Luthfika Dewi; Sani Ega Priani (UNISBA Press, 2022)
Abstract. Skin is the outermost organ of the body that lines the human body. The skin has a bad effect if it is exposed to the sun for too long. Therefore, skincare is very necessary to keep the skin healthy, beautiful, and looks clean. One way is to use a face mask. Masks are one of the skincare cosmetics. The special characteristic of the mask preparation is that it is easy to use and clean. One of the most popular facial mask preparations is the clay-based wash-off type, which is often referred to as clay facial masks or by the market name